Návrh aplikace Dashboard pro společnost Vodafone Czech Republic a.s - Bartoň, Roman (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce pojednává o novém návrhu aplikace Dashboard pro společnost Vodafone Czech Republic. Aplikace Dashboard slouží k monitoringu prodeje na značkových prodejnách společnosti. Cílem práce je navrhnout zbrusu novou aplikaci v prostředí VBA a rozšířit její funkcionalitu o nové statistické a motivační ukazatele. Tyto prvky poslouží ke zvýšení výkonnosti prodejců a navíc podpoří analytické možnosti vedoucího prodejny.

The thesis deals with the new design of Dashboard application developed for Vodafone Czech Republic company. The application serves for sales monitoring on all direct retail stores of the company. Major goal of this project is to design a brand new application and enhancing its functionality with new analytical tools and motivational indicators. These innovations will empower the performance of salesmen along with providing the new analytical possibilities for store managers.
Design of the Dashboard Application for Vodafone Czech Republic Company
Keywords: Dashboard; Vodafone; Motivace; VBA; Excel; Formulář; Hodnocení; Design; Dashboard; Vodafone; Motivation; VBA; Excel; Form; Evaluation; Design